Christian Education Through Mapalus Culture in North Minahasa District - Tumundo, Deyvi; Undap, Andy P.P.; Poluan, Agnes Relly (International Journal of Education, Information Technology, and Others, 2024)
Mapalus culture is a practical form of the Sitou Timou Tumou Tou philosophy, which is an activity of community life with the nature of mutual cooperation (cooperation) which is inherent in every human being, son and daughter of the Minahasa ethnic community. Mapalus literally means mutual cooperation or cooperation. Its application in people's lives includes almost all work, whether in mourning (misfortune), Mapalus culture contains very strong Christian values ​​such as family, love and peace. The impact of modernization with various technological advances is starting to displace shared values. From this background, the researcher felt interested in researching "Christian Education through Mapalus Culture in Kauditan District, North Minahasa Regency". In this study the researcher attempted to study and analyze: 1) Perceptions of Christian Education carried out through Mapalus culture in Kec. District audit. North Minahasa. 2) Supporting Factors of Christian Education through the culture of Mapalus District. District audit. North Minahasa. 3) Inhibiting Factors of Christian Education through Mapalus Culture, Kec. District audit. North Minahasa. 4) Mapalus Cultural Efforts as a strategy for Christian Education in Kec. District audit. North Minahasa. The research method used in this research is a qualitative approach with phenomenological methods. The phenomenological method is a research method that seeks to build an understanding of reality. Researchers obtained information related to Mapalus cultural research from research objects (informants/community in Kauditan District). From this research, the researchers found: 1) Mapalus culture is a way of life that loves each other for the Minahasa people. In other words, Mapalus Culture is a real manifestation of Christian Education in Minahasa society. 2) The process of forming Christian religious education relies heavily on the implementation of Mapalus culture, because Mapalus culture is a medium that conveys Christian education to the Kauditan community as a whole. 3) When there is an event, whether sad or happy, young people tend to only collect money and not involve themselves directly as a real form of solidarity. 4) Actively involving the community in the preservation and development of Mapalus culture, such as through volunteer activities, farmer groups, or local cultural organizations such as rukun mourning, rukun marriage is part of the effort to ensure that this culture remains